Farm planning for a typical crop-livestock integrated farm : an application of a mixed integer linear programming model - Ghebretsadik, Amanuel Habte (Stellenbosch : Stellenbosch University, 2012)
Assignment (MSc) -- University of Stellenbosch, 2004.